The Dino Study: Rationale and protocol for a randomized controlled trial of the Incredible Years Dinosaur Program with daily assessments - Rabia R. Chhangur; Eleonore H.M. Smalle; Gerdien van der Zwaag; Egon Dejonckheere (PLoS ONE, 2025)
Background Children with conduct problems vary considerably in how they respond to behavioral interventions. Although group-based, child-focused programs are increasingly implemented, research still relies on retrospective parent or teacher reports and group-level outcomes. These traditional approaches often obscure individual differences in treatment response and reduce the potential for individualized behavioral support tailored to each child’s unique profile. The Dino Study—Daily Intervention-based research on Nurturing Opportunities—introduces the Incredible Years Dinosaur Program in the Netherlands for children aged 4–8 with conduct problems. This evidence-based program, grounded in cognitive-behavioral principles, aims to strengthen children’s emotional regulation, social skills, and problem-solving through structured, play-based group sessions. However, little is known about mechanisms of change in children’s daily life, particularly how emotional and behavioral improvements unfold within and across individual children during intervention. This study evaluates the program’s effectiveness in reducing externalizing behavior and promoting cognitive and prosocial functioning, and explores daily variability in children’s emotional and behavioral responses using a daily diary design. Methods This protocol outlines a randomized controlled trial with a waitlist control condition. A total of 120 children will be randomly assigned (1:1) to the intervention or waitlist group. Participants will be recruited via professional institutions and primary schools in both preventive and clinical contexts. In addition to pre- and post-assessments, Intensive Longitudinal Data (ILD) will be collected to capture daily fluctuations in mood, behavior, and family interactions before, during, and after the intervention. This design enables analysis of group-level effects as well as intra-individual change patterns. Expected outcomes Findings will offer novel insights into how children respond individually to structured interventions in real-life settings and inform more personalized, ecologically valid approaches to early behavioral support. Trial registration ClinicalTrials.gov ( NCT07051642 ).